Afzelin Prevents against Lipopolysaccharide-Induced Acute Lung Injury and Sepsis via Inhibiting the Inflammatory Mediators - Zhao, Honghui (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: One of the main causes of death in critical care units and a serious consequence of sepsis is Acute Lung Injury (ALI). Studies have shown that afzelin reduces inflammation and oxidative damage. However, the potential protective effects of afzelin's anti-inflammatory and antioxidative activities against Lipopolysaccharide (LPS)-induced ALI and sepsis remain unclear. Materials and Methods: Male Wistar albino rats were injected intraperitoneally with LPS (5 mg/kg) in order to develop an ALI model. The rats were split up into 3 groups: group I was the control group, group II was the LPS-treated control group, and group III was the Afzelin-treated group. Results: Increased levels of lung damage, inflammatory cytokines, MDA, NO, ROS, and W/D ratio were seen in the animals in group II. The animals in group II had lower antioxidant levels. Treatment with afzelin significantly decreased the amount of lung damage, inflammatory cytokines, MDA, NO, ROS, and the W/D ratio of the lungs in the LPS triggered rats. Furthermore, it raised the antioxidant content of the lung tissue. In the current study, nursing care for patients with acute lung disease emphasizes the importance of continuous monitoring, counselling, and providing essential support. However, further clinical trials are required to evaluate the safety and efficacy of these interventions. Conclusion: In summary, afzelin can ameliorate ALI induced by LPS through anti-oxidative and its anti-inflammatory effect.
Keywords: Acute lung injury; Lipopolysaccharide; Afzelin; Anti-oxidative; Anti-inflammatory